Morbidity profile of ex-servicemen residing in Sangli-Miraj-Kupwad municipal corporation area and its relationship with certain clinico-epidemiological factors - Kumbhar S; Joshi J; Tapare V; Yadav J (Indian Journal of Community Medicine, 2007)
Research Question: What is the morbidity profile of ex-servicemen residing at Sangli-Miraj-Kupwad corporation area. Objectives: 1) To determine types and extent of prevalent morbidities among ex-servicemen. 2) To ascertain the association between prevalent morbidities and selected predictor variables Study Design: Cross-sectional study. Setting: Ex-servicemen′s canteen, Vishrambag, Sangli. Participants: 416 ex-servicemen, registered under ex-servicemen′s canteen, Vishrambag. Statistical Analysis: Percentage, Chi-square test, and odds ratio. Results: 214 (52.16%) subjects had one or more diseases/conditions. Commonest diseases detected were hypertension (26.20%), musculoskeletal problems (23.55%), and mental health problems (12.98%). Increase in the post-retirement period of ex-servicemen was significantly associated with increase in prevalence of hypertension, OR = 10.88 (4.54-26.52) and musculoskeletal disorders, OR = 8.75 (3073-20.52). Prevalence of hypertension was significantly more for those who served less than 10 years in the military job, OR = 1.90 (1.04-3.8). In the upper socio-economic class, the risk of hypertension was significantly more, OR = 6.08 (1.78-20.17); in the upper lower class, the risk of musculoskeletal disorders was significantly more, OR = 4.15 (1.88-9.16). Considering the importance of health of ex-servicemen and existence of high morbidity pattern, periodical screening was needed for every ex-serviceman who belonged to the high-risk group.